What can moment-by-moment learning curves tell about students' self-regulated learning?. (April 2021) - Molenaar, Inge; Horvers, Anne; Baker, Ryan S.
Abstract: Many students in primary education learn arithmetic using adaptive learning technologies (ALTs) on tablets every day. Driven by developments in the emerging field of learning analytics, these technologies adjust problems based on learners' performance. Yet, until now it is largely unclear how students regulate their learning with ALTs. Hence, we explored how learners regulate their effort, accuracy and learning with an ALT using moment-by-moment learning curves. The results indicated that moment-by-moment learning curves did reflect students' accuracy and learning, but no associations with effort were found. Immediate drops were associated with high prior knowledge and suboptimal learning. Immediate peaks were associated with robust learning and pointed to effective student regulation. Close multiple spikes showed moderate learning and lower initial levels of accuracy but, with system support, these students seemed able to regulate their learning. Separated multiple spikes indicated reduced learning and accuracy and potentially signal the inability of students to regulate their learning. In this light, moment-by-moment learning curves seem to be valuable indicators of accuracy regulation during learning with ALTs and could potentially be used in interventions to support SRL with personalized visualizations. Highlights: Children show differential effort and accuracy regulation while learning with ALTs. Moment-by-moment learning curves are associated to childrens' accuracy and learning . Moment-by-moment learning curves are indicative learners efficiency of regulation over time.